ON THE ISSUE OF OPERATIONAL RATIONING OF ENERGY RESOURCES FOR TRAIN TRACTION - Красулін, Олександр (SWorldJournal, 2024)
The task of resource conservation is relevant for all transport companies, and many global communities of scientists and engineers are looking for ways to solve it. Global railway companies, and especially such large ones as UZ, are major consumers of ene